Digital forensic analysis of intelligent and smart IoT devices - Kim, Minju; Shin, Yeonghun; Jo, Wooyeon; Shon, Taeshik (Journal of Supercomputing, 2023)
AI is combined with various devices to provide improved performance. IoT devices combined with AI are called smart IoT. Smart IoT devices can be controlled using wearable devices. Wearable devices such as smartwatches and smartbands generate personal information through sensors to provide a range of services to users. As the generated data are preserved in the storage of the wearable device, getting access to these data from the device can prove useful in criminal investigations. We, therefore, propose a forensic model based on direct connections using wireless or interfaces beyond indirect forensics for wearable devices. The forensic model was derived based on the ecosystem of wearable devices and was divided into logical and physical forensic methods. To confirm the applicability of the forensic model, we applied it to wearable devices from Samsung, Apple, and Garmin. Our results demonstrate that the proposed forensic model can be successfully used to derive artifacts.
Keywords: Criminal investigation; Digital forensic analysis; Forensic models; Model-based OPC; Performance; Personal information; Smartband; Smartwatch; Wearable devices; Wearable ecosystem; Digital forensics; Smartband; Smartwatch; Wearable ecosystem